Nigrostriatal Degeneration in the Cognitive Part of the Striatum in Parkinson Disease Is Associated With Frontomedial Hypometabolism. (February 2020) - Apostolova, Ivayla; Lange, Catharina; Frings, Lars; Klutmann, Susanne; Meyer, Philipp T.; Buchert, Ralph
Abstract : Purpose: The present study investigated possible associations between cortical dysfunction/degeneration as measured by 18 F-FDG PET and nigrostriatal degeneration according to the specific 123 I-FP-CIT binding ratio (SBR) in striatal subregions defined by striato-cortical anatomical connectivity in Parkinson disease (PD) patients. Materials and Methods: The study included 41 patients (61.4 ± 12.8 years) with PD-typical reduction of striatal FP-CIT SBR and no sign of atypical parkinsonian syndrome on FDG PET. FP-CIT SBR was determined separately in the cognitive (composite of executive and limbic) and sensorimotor part of the striatum according to the Oxford-GSK-Imanova Striatal Connectivity Atlas. Scaled FDG uptake was tested voxelwise for correlation with FP-CIT SBR (familywise error corrected P < 0.05). Results: A large cluster (17.6 mL) of significant correlation of scaled FDG uptake with FP-CIT SBR in the cognitive part of the striatum, corrected for SBR in the sensorimotor part, was detected in the bilateral medial frontal cortex and the anterior cingulate cortex (partial correlation coefficient R = 0.767); small clusters were detected in ipsilateral caudate and ipsilateral thalamus. There was a small contralateral occipital cluster (3.0 mL) of significant correlation between FDG uptake and sensorimotor SBR corrected for cognitive SBR ( R = 0.709). Conclusions: The correlation between nigrostriatal degeneration in the cognitive striatum and reduced cerebral glucose metabolism in the medial parts of the frontal cortex including the anterior cingulate suggests that nigrostriatal degeneration is specifically involved in the pathogenesis of cognitive deficits associated with medial frontal dysfunction such as impaired inhibitory control. Abstract : Supplemental digital content is available in the text.